Analisis Konsentrasi DNA dan Prediksi Protein Coral - Hamid Hamid; Iman Supriatna; Endang Gunaisah; Muhsuryono Muhsuryono; Ismail Ismail; Abdul Gofir (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2015)
This study aimed to determine the concentration of DNA and proteins Coral predictions based on data from GenBank. DNA isolation technique Pocillopora sp. using tissue and blood DNeasy Kit (Qiagen). DNA concentrations were analyzed using a spectrophotometer and Corl protein prediction by comparing the primers used by the data GenBank (NCBI). DNA concentration of each sample varies between 5.0 ng/µl-20.8 ng/µl in the first purification and between 3.0 ng/µl - 8 ng/µl, where the highest concentration of DNA present in the sample HC2. DNA concentration and purity of samples obtained at HC2 and HC3. Prediction of protein based on data GeneBank is homologous with a NADH dehydrogenase in Coralliumkonojoi